Mechanical properties and microstructural characteristics of rotary friction welded dissimilar joints of rolled homogeneous armor steel and medium carbon steel - Karthick K. (De Gruyter, 2021)
Distinct materials are used for the construction of battle tanks used in defense sectors. The hull and turret of the battle tanks are made up of rolled homogeneous armor steel (also known as armor steel). The inner portions like the driver cabin and control room are covered with medium carbon steel. Hence, the dissimilar joint between these materials is unavoidable in the battle tank construction. Conventional fusion welding processes like manual metal arc welding, gas metal arc welding, and gas tungsten arc welding are preferred to join the dissimilar metals. However, the high heat input nature of these processes will create hydrogen induced cracking, high residual tensile strain, and HAZ softening, etc. To minimize these issues, solid state welding processes were adopted. In the present study, mechanical properties and microstructural characteristics of rotary friction welded dissimilar joint of armor steel and medium carbon steel was analyzed. The ultimate tensile strength of the dissimilar joint is around 775 MPa and the failure occurred at the medium carbon steel side. The impact toughness value of dissimilar joints is higher than medium carbon steel and lower than armor steel. The microstructure across the dissimilar joint has distinct features and a complex pattern was observed at the weld interface.